Sleep, diet, activity, and incident poor self-rated health: A population-based cohort study - Oftedal, Stina; Rayward, Anna T; Fenton, Sasha; Duncan, Mitch J (My University, 2021)
The prospective relationships between poor sleep health, poor diet quality, and physical inactivity with self-rated health (SRH) are not well described. The aim of this study was to assess individual and joint associations between high-risk health behaviors and incident poor SRH. Participants from the Household Income and Labor Dynamics in Australia longitudinal cohort reporting "good" SRH in 2013 were included (n = 8,853) in 2020 data analysis. Logistic regression was used to assess odds of poor SRH in 2017 associated with (a) individual, (b) count, and (c) unique combinations of high-risk behaviors reported in 2013. In the sample (48% female, Mage = 45.2 years, SD = 16.8), poor sleep health (OR = 1.66, 95% CI [1.38, 2.01]), physical inactivity (OR = 1.18, [1.01, 1.38]), and poor diet quality (OR = 1.38, [1.16, 1.65]) were associated with increased odds of poor SRH. Reporting one (OR = 1.76, [1.27, 2.43]), two (OR = 2.16, [1.57, 2.98]), and three (OR = 2.99, [2.02, 4.41]) high-risk behaviors was associated with increased odds of poor SRH. All unique combinations of high-risk behaviors were significantly associated with greater odds of poor SRH, except "poor sleep health only" (prevalence = 1.3%). Odds of poor SRH associated with high-risk behavior combinations ranged from 1.73 (95% CI [1.21, 2.47]) for "physical inactivity only" to 4.11 ([2.66, 6.35]) for "poor sleep health + poor diet quality." Reporting ≥ 1 high-risk behavior was associated with increased odds of poor SRH. The combination of poor sleep health with poor diet quality was associated with the greatest odds of poor SRH. Improving multiple high-risk behaviors in combination may be more effective in preventing decline in SRH than improving any behavior alone. (PsycInfo Database Record (c) 2021 APA, all rights reserved).
Health Psychology
Keywords: Health and wellbeing; Lifestyle